2022
DOI: 10.1002/oby.23547
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of the Communicating Healthy Beginnings Advice by Telephone trial for early childhood obesity prevention

Abstract: Objective: This study aimed to conduct an economic evaluation of the Communicating Healthy Beginnings Advice by Telephone (CHAT) trial to prevent childhood obesity.Methods: Cost-effectiveness analyses were conducted for the telephone and short message service (SMS) delivery of Healthy Beginnings advice, compared with usual care, which included child health services unrelated to Healthy Beginnings. Costs were valued in 2018 Australian dollars, and costs and outcomes were discounted at 5% per year. The costs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…192 Rates of 3% were typical in the United States and Australia, but the most recent studies in Australia applied a 5% discount rate to costs and benefits. [48][49][50]177 Across all studies, discount rates did not exceed 5%. Many studies with follow-up periods or time horizons exceeding 1 year did not report discount rates, and no justification was provided for their omission.…”
Section: Discountingmentioning
confidence: 87%
See 4 more Smart Citations
“…192 Rates of 3% were typical in the United States and Australia, but the most recent studies in Australia applied a 5% discount rate to costs and benefits. [48][49][50]177 Across all studies, discount rates did not exceed 5%. Many studies with follow-up periods or time horizons exceeding 1 year did not report discount rates, and no justification was provided for their omission.…”
Section: Discountingmentioning
confidence: 87%
“…60,61,67,75,76,106,107,109,111,112,167 The economic evaluation of e-health interventions ("the use of information and communications technology in support of health and health-related fields" 184 ) and interventions with m-health (a subset of ehealth based on mobile wireless technologies 185 ) components at their core emerged only within the past 5 years. 47,48,79,113,114,133,142,171,177 The costing of these interventions reveals contemporary complexities attended by the omission of associated resource use and costs. One study excluded costs relating to research and development of a multicomponent m-health intervention, 133 while another study reported difficulties obtaining similar costs.…”
Section: Study Characteristics Across All Intervention Groupingsmentioning
confidence: 99%
See 3 more Smart Citations